1995
DOI: 10.1093/jac/36.1.259
|View full text |Cite
|
Sign up to set email alerts
|

A placebo controlled evaluation of lomefloxacin in the treatment of bacterial diarrhoea in the community

Abstract: We compared 40 patients taking lomefloxacin 400 mg once daily for 5 days in a double blind trial with 44 placebo takers with proven community acquired bacterial diarrhoea (85% due to Campylobacter spp.). Lomefloxacin eradicated Campylobacter spp. in 75% but did not alter clinical outcome. Twenty-eight per cent of the campylobacter isolates developed resistance. Thirty-three per cent developed side-effects. Lomefloxacin is not recommended for community-acquired bacterial diarrhoea when Campylobacter spp. predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…However, Campylobacter has become increasingly resistant to FQ antimicrobials. Although FQ-resistant (FQ R ) Campylobacter occurs in clinical settings (13,14), poultry are considered a significant source of FQ R Campylobacter, because FQ antimicrobials have been used for the production of meat chickens, and the majority of domestically acquired cases of human campylobacteriosis result from consumption of undercooked chicken or food contaminated by raw chicken (11,15). Therefore, reducing the occurrence and spread of FQ R Campylobacter in poultry is considered an important step in the control of foodborne campylobacteriosis.…”
mentioning
confidence: 99%
“…However, Campylobacter has become increasingly resistant to FQ antimicrobials. Although FQ-resistant (FQ R ) Campylobacter occurs in clinical settings (13,14), poultry are considered a significant source of FQ R Campylobacter, because FQ antimicrobials have been used for the production of meat chickens, and the majority of domestically acquired cases of human campylobacteriosis result from consumption of undercooked chicken or food contaminated by raw chicken (11,15). Therefore, reducing the occurrence and spread of FQ R Campylobacter in poultry is considered an important step in the control of foodborne campylobacteriosis.…”
mentioning
confidence: 99%
“…Although FQ resistance in Campylobacter can occur following the treatment of humans with the antibiotic (4,17,22), poultry are considered a significant source for FQ-resistant Campylobacter (1,5,7,18). Laboratory studies have demonstrated the emergence of FQ-resistant Campylobacter in experimental chickens treated with FQ antibiotics (10,12).…”
mentioning
confidence: 99%
“…Two were withdrawn from the trial after developing anaphylactoid reactions. 23 In the same trial, 18% of treated participants developed organisms resistant to lomefloxacin.…”
Section: Harmsmentioning
confidence: 99%
“…We found 9 randomized controlled trials in 8 reports [20][21][22][23][24][25][26][27] (1,760 participants) 21 Entry criteria varied between trials, and treatment duration ranged from a single dose to 5 days. In 3 trials, antibiotics reduced illness duration 24,27 or decreased the number of liquid stools by 48 hours, 20 whereas in 5, illness duration was not reduced.…”
Section: Benefitsmentioning
confidence: 99%
See 1 more Smart Citation